Determinants Of Financial Distress In Retail Trade Sub-Sector Companies In Indonesia - Fathurachman, Fathurachman (GOVERNORS, 2024)
This study aims to identify the influence of cash flow, sales growth, liquidity, and profitability on financial distress. This study uses a quantitative approach by utilizing secondary data in the form of company financial statements. The population in this study is companies that belong to the retail trading sub-sector listed on the Indonesia Stock Exchange. The purposive sampling method was used to select 12 companies as research samples. The analysis method used is multiple linear regression. The results showed that cash flow, sales growth, and liquidity had a significant negative influence on financial hardship, which meant that an increase in these three variables tended to lower the risk of financial hardship. Meanwhile, the profitability variable did not show a significant influence on financial difficulties, indicating that the level of profitability was not directly related to the financial condition of the company that was experiencing difficulties. These findings provide important insights for company management in managing financial risks.